Gene Mutations in Esophageal Mucosa of Chagas Disease Patients - Manoel-Caetano, Fernanda da Silva [UNESP]; Silveira, Aparecida F. P. [UNESP]; Silva, Ana Elizabete [UNESP] (Int Inst Anticancer Research, 2009)
Background: Chagas disease patients with longstanding megaesophagus have a significantly increased risk for esophageal carcinoma. Materials and Methods: PCR-SSCP analysis and DNA sequencing of esophageal mucosa from Chagas disease patients (with or without megaesophagus) in the exons of the TP53, CDKN2A and FHIT genes were performed. Results: SSCP analysis showed a mobility shift in 2120 patients with grade IV megaesophagus (CDKN2A exon 1 and FHIT exon 7) and in 1/10 patients without megaesophagus (TP53 exons 5 and 8). However, DNA sequencing indicated a silent mutation in exon 7 of the FHIT gene (GCT -> GCC) in codon 88 in only one case of megaesophagus. Conclusion: Gene mutations are rare events in the exons investigated in esophageal mucosa of Chagas disease patients and further investigations are important to clarify the possible involvement of this silent mutation in exon 7 (FHIT gene) in the advanced grades of megaesophagus and esophageal carcinogenesis.
Keywords: Chagas disease; Megaesophagus; gene mutation; single nucleotide polymorphism (SNP); FHIT gene; TP53 gene; CDKN2A gene; DNA sequencing